Framework for flood risk management in urban basins under non-stationary scenarios based on hydrological-hydrodynamic simulations - Navarro, Fabricio Alonso Richmond (2024)
The accelerated loss of vegetation cover and the increasing sealing of urban areas are changing the patterns of rainwater runoff and infiltration. On the other hand, the effects of climate change are altering precipitation regimes according to global model projections. These elements have increased the frequency and intensity of flooding in urban areas in recent years. The population, urban authorities, and the various economic sectors have shown a limited capacity to adapt to these constantly evolving changes. This combination of factors increases the three main components of risk - hazard, exposure, and vulnerability - leading to important losses for all urban stakeholders. Structural and non-structural measures are currently being adopted to mitigate these consequences. However, these solutions often prove ineffective against extreme events, especially regarding traditional mitigation measures. It is, therefore, essential to develop innovative solutions to strengthen the resilience of cities, combining the valorization of natural capital and urban ecohydrology in mitigating natural disasters with non-structural adaptation strategies to extreme events. In this sense, a multi-stage framework for flood risk management in urban basins under non-stationary scenarios is presented, which analyzes the use of pre-event mitigation measures, such as nature-based solutions (NbS) or gray infrastructure, with subsequent adaptation processes, in a context of accessible communication of information. To this end, hydrological-hydrodynamic simulations were used in non-stationary scenarios for various planning horizons, considering changes in land use and cover resulting from various socio-economic narratives and changes in precipitation intensity. The multi-stage framework makes it possible to identify potential flood damage reduction through mitigation measures. It encourages adaptation processes by quantifying the areas at risk and the maximum potential post-event damage, suggesting protecting them through water insurance. The case study in the urban basins of São Carlos/São Paulo illustrates the application of the flood risk management framework. The results show that urban basins should consider mitigation and adaptation measures consistent with their socio-economic development in the coming years, as proactive and sustainable societies will face fewer challenges than reactive, isolated societies with high waterproofing rates. It is concluded that the current mitigation measures used in the basins may be insufficient for aggressive future non-stationary scenarios. These must, therefore, be complemented with adaptation measures such as water insurance and changes in land use and cover. This framework aims to show the need to adapt urban basins to raise awareness among the population and local governments, thus stimulating innovative combinations of mitigation and risk transfer mechanisms to increase the resilience of cities.